2022
DOI: 10.1002/2211-5463.13387
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes: multifunctional compartments ruled by a complex regulatory network

Abstract: More than 50 years have passed since Nobel laureate Cristian de Duve described for the first time the presence of tiny subcellular compartments filled with hydrolytic enzymes: the lysosome. For a long time, lysosomes were deemed simple waste bags exerting a plethora of hydrolytic activities involved in the recycling of biopolymers, and lysosomal genes were considered to just be simple housekeeping genes, transcribed in a constitutive fashion. However, lysosomes are emerging as multifunctional signalling hubs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…The mammalian target of rapamycin complex 1 (mTORC1) plays a central role in sensing the cellular state and regulating TFEB activation [42,63,69]. The mTORC1/TFEB axis responds to various stimuli in the microenvironment, regulates several aspects of the cellular physiology, and coordinates lysosomal biogenesis and autophagy [63,70].…”
Section: History Of Tfeb In the Autophagolysosomal System Lysosomal A...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian target of rapamycin complex 1 (mTORC1) plays a central role in sensing the cellular state and regulating TFEB activation [42,63,69]. The mTORC1/TFEB axis responds to various stimuli in the microenvironment, regulates several aspects of the cellular physiology, and coordinates lysosomal biogenesis and autophagy [63,70].…”
Section: History Of Tfeb In the Autophagolysosomal System Lysosomal A...mentioning
confidence: 99%
“…In addition, other regulators, such as members of the MITF family, AMPK, Wnt, p53, PtdIns3P, microRNAs/miRNAs, etc., function in autophagy [39][40][41]. Lysosomes are regulated by a sophisticated system to meet cellular needs when the microenvironment changes; that is, they have multiple functions, and lysosomal proteins are not merely constitutively transcribed from housekeeping genes [42]. Because lysosomes and autophagy machinery are both sophisticated and intimately related, the number of studies directed to the core regulators of the autophagolysosomal system is constantly increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Jonathan Martinez‐Fabregas, a member of the journal's EAB, served as a guest editor of our special lysosomes issue. This issue contained five Review articles focussed on the important role of lysosomes, once thought to be little more than waste disposal units, in health and disease: in their article, Jonathan Martinez‐Fabregas, Irene Díaz‐Moreno and colleagues indicated that the lysosome is part of a complex communication network between organelles, and lysosome dysfunction is linked to a variety of pathologies [ 1 ]. These disease states include cancer and neurodegeneration, as reviewed by Janko Kos and co‐authors in the same issue [ 2 ].…”
Section: New Developments In 2022mentioning
confidence: 99%